DIVISION IX: COMMISSION 30: RADIAL VELOCITIES. (13th August 2015) - Torres, Guillermo; Pourbaix, Dimitri; Udry, Stephane; Marcy, Geoffrey W.; Mathieu, Robert D.; Mazeh, Tsevi; Minniti, Dante; Moutou, Claire; Pepe, Francesco; Turon, Catherine; Zwitter, Tomaz
Abstract : The meeting was attended by the President and Vice-President of the Commission, along with approximately 15 other members. The President reported on the election of new officers that took place at the end of March 2012, for four new members of the Organizing Committee as well as a new Vice-President, and thanked the outgoing members. Tomaz Zwitter (Slovenia) was elected as the new VP (2012–2015), and the new OC members for the period 2012–2018 are Alceste Bonanos (Greece), Alain Jorissen (Belgium), David Katz (France), and Matthias Steinmetz (Germany). The current VP, Dimitri Pourbaix, became the President through 2015.